Non-intellective factors in the high school academic achievement of high ability students - Ramirez, Angelina E. 1919-
This is an analysis of the roles of eight personality dimensions in academic achievement. It identifies the nature and method of adjustment associated with either "good" or "poor" academic performance. Designed as an ex post facto triple experiment, this investigation made use of three sets of statistically equivalent matched groups of high school senior students.